Comparison of the Effectiveness of Cognitive Behavioral Therapy and Acceptance and Commitment Therapy on Reducing Mood Symptoms in Patients With Substance Abuse - Haghighat, Sara; Mohammadi, Alireza (International Clinical Neuroscience Journal, 2018)
Background: The purpose of this study was to compare the effectiveness of cognitive-behavioral therapy (CBT) and acceptance and commitment therapy (ACT) on reducing mood symptoms in patients with substance abuse. Methods: The current research was a semi-experimental study with pre-test and post-test with a control group. The participants consisted of all people with substance abuse referred to drug abuse treatment centers in district 4 and 8 of Tehran city in 2016-2017. In this way, 45 subjects selected by purposeful sampling method and randomly divided into 2 groups of experimental and one control group (15 persons for each group). Then, the Mood Disorder Questionnaire and Depression Inventory took from the subjects of each group. CBT and ACT performed in 8 sessions of 90 minutes in 2 experimental groups and control group were also without any training program. After completing the training, the post-test performed for all three groups. Data analysis was done by using the covariance analysis (MANCOVA) and using SPSS-21 software. Results: The findings showed that CBT and ACT were effective in reducing mood syndrome in patients with substance abuse (P<00.001). Moreover, there were no significant differences between the effectiveness of the CBT and ACT on the reduction of mood syndrome in patients with substance abuse. Conclusion: Considering the effect of CBT and ACT on the reduction of mood syndrome among patients with substance abuse, it is worth considering the role of these 2 treatments as one of the educational and therapeutic strategies for substance abuse.